(untitled) (Journal of Parents and Teachers, 1997)
Consumer education is integrated into the school curriculum as a cross-cutting theme, promoting the formation of critical and responsible citizens. It focuses on reflection on production, the environment and consumer rights. Teacher training is key to implementing educational projects that promote consumer awareness and responsibility.